Akademska zvanja i osiguranje kvalitete: Izazovi normativnih okvira De lege ferenda / Academic Titles and Quality Assurance: Challenges of Legal De lege ferenda Frameworks - Hebib, Mirza (Pregled: časopis za društvena pitanja / Periodical for social issues, 2023)
The leading argument of this article is that status issues of academic staff in the context of quality assurance should be addressed through the application of comparative law, respecting the guarantee of academic autonomy, principles of academic freedom, academic self-government, pluralism of scientific disciplines and preservation of scientific production of national importance. All of the above is correlated with the creation of an environment in which the criteria for academic advancement will be more demanding than the existing ones, while respecting the overall valorization of academic work. Changes in normative frameworks must be aimed at better quality research and teaching work and stronger competitiveness of the University of Sarajevo in the European environment. Reforms need to be implemented thoughtfully, based on analyzes with identified problems and goals to be achieved, taking into account the BiH social context and the current general legal framework in which the University of Sarajevo exists, as the largest and most important higher education institution in Bosnia and Herzegovina.